Impact of SHG on Income of Pig Farmers in Mizoram of North East India - Hmingthanzuala,; Das, Samares Kumar; Rahman, Saidur; Tolenkhomba, T. C.; Saikia, Prasanta (International Journal of Bio-resource and Stress Management, 2023)
The success of Bangladesh Grameen Bank has made microfinance a means for providing credit to the poor through Self-help Groups (SHGs). Mizoram is one of the eight states in north-eastern India. Self Help Groups (SHGs) is being formed by government agencies such as National Bank for Agriculture and Rural Development (NABARD), District Rural Development Agency (DRDA), etc. Also several NGOs are forming SHGs such as World Vision, Open Doors, Goodwill, etc. Piggery plays a role in the economy of the state more than other livestock. Pig-rearing is an important SHG activity. But negligible studies have been conducted on the SHGs in Mizoram. Keeping this in view, present study was undertaken in Serchhip and Kolasib district where pig-rearing SHGs are formed by National Rural Livelihood Mission (NRLM). Twenty Self-help Groups (SHGs) engaged in pig-rearing activity was studied to measure the impact of SHG on income of its members. The study was conducted in purposively selected two districts having four rural development blocks. Five SHGs from each block and five SHG members from each of 20 SHGs were selected randomly. Total 100 SHG members were interviewed. Paired t−test showed significant increase in income after joining the group. Study concludes that pig rearing can be undertaken by SHGs to improve the economy of the people. There is a need to study the sustainability of pig-rearing SHGs in the study area.